2014
DOI: 10.3390/molecules190915339
|View full text |Cite
|
Sign up to set email alerts
|

Surface Properties and Photocatalytic Activity of KTaO3, CdS, MoS2 Semiconductors and Their Binary and Ternary Semiconductor Composites

Abstract: Single semiconductors such as KTaO3, CdS MoS2 or their precursor solutions were combined to form novel binary and ternary semiconductor nanocomposites by the calcination or by the hydro/solvothermal mixed solutions methods, respectively. The aim of this work was to study the influence of preparation method as well as type and amount of the composite components on the surface properties and photocatalytic activity of the new semiconducting photoactive materials. We presented different binary and ternary combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 47 publications
(51 reference statements)
0
22
0
Order By: Relevance
“…From the absorption spectrum comparison of the three samples, it can be known that the absorption capacity of the spectrum absorption intensity in the range of 400 nm to 800 nm is MoSe 2 > MoSSe > MoS 2 , which is consistent with the literature. [25][26][27] The UV-vis spectra show that the absorption edges of MoSSe, MoS 2 and MoSe 2 are about 826 nm, 760 nm, 864 nm, respectively. According to the formula: 28 E ðeVÞ ¼ hc l , where E, h, l and c are the band gap energy of the semiconductor material, Planck constant, wavelength of light and speed of light, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…From the absorption spectrum comparison of the three samples, it can be known that the absorption capacity of the spectrum absorption intensity in the range of 400 nm to 800 nm is MoSe 2 > MoSSe > MoS 2 , which is consistent with the literature. [25][26][27] The UV-vis spectra show that the absorption edges of MoSSe, MoS 2 and MoSe 2 are about 826 nm, 760 nm, 864 nm, respectively. According to the formula: 28 E ðeVÞ ¼ hc l , where E, h, l and c are the band gap energy of the semiconductor material, Planck constant, wavelength of light and speed of light, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Nanocomposites were obtained by one-pot synthesis (named 1-step hydrothermal mixing solutions) and by 2-step hydrothermal synthesis as was recently reported by us for KTaO 3 -CdS-MoS 2 nanocomposites [19]. In one-pot synthesis rout, all reagents in specified molar ratio of products were mixed, transferred into autoclave and thermally treated under the selected conditions.…”
Section: Synthesis Of Binary and Ternary Combinations Of Semiconductorsmentioning
confidence: 99%
“…Zaleska et al prepared a series of novel binary and ternary composite photocatalysts based on the combination of KTaO 3 , CdS and MoS 2 semiconductors via hydro/solvothermal precursor route. They found that the highest photocatalytic activity toward phenol degradation under both UV-Vis and visible light irradiation and superior stability in toluene removal was observed for ternary hybrid obtained by calcination of KTaO 3 , CdS and MoS 2 powders at the 10: 5: 1 molar ratio [43].…”
Section: Heterojunction Of Nano-/microarchitecturesmentioning
confidence: 99%